Діагностика автоімунного тиреоїдиту у жінок із гінекологічними захворюваннями - Хабрат, Б. В.; Литвак, О. О.; Гирявенко, О. Я.; Лисенко, Б. М.; Хабрат, А. В.; Ларіна, О. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
The estimation of the main echographic signs of autoimmune thyroiditis with various gynecological diseases: uterine fibroids, endometriosis and inflammatory diseases of the appendages was made. The most informative diagnostic markers of this disease with the various gynecological diseases were proposed.